Clustering Pengunjung Mall Menggunakan Metode K-Means dan Particle Swarm Optimization - Teuku Muhammad Dista; Ferian Fauzi Abdulloh (STMIK Budi Darma, 2022)
This research aims to cluster mall visitors. This is motivated by the mall's income which has decreased since the pandemic. Later from these several clusters we can find out the characteristics of the mall's visitors. Those characteristics will be used later to increase the income from the mall. In this research, we use a dataset from Kaggle named Pengunjung_mall in CSV format which will later be processed using Python language on Jupiter Notebooks using the K-Means method. To ensure how accurate the K-Means method is, optimization is carried out using the PSO (Particle Swarm Optimization) method. After performing clustering and optimization using Jupyter Notebook, the results will then be evaluated with DBI (Davies Bouldin Index) in Microsoft Excel to find out how well the Clustering is generated. The Clustering results obtained are used as a reference to determine the characteristics of mall visitors which is one strategy to increase Mall profits. As a result, we have succeeded in dividing mall customers into 5 clusters based on their annual earned income and expense scores. The cluster has been optimized with PSO and has succeeded in increasing the cluster resulting from the K-Means method which is proven by the Davies Bouldin Index method. This research has concluded that customers who have high income levels and have high spending scores are the targets with the highest priority level for malls.